Optimising the use of biocontrol agents to improve the control of botrytis cinerea in key vegetable and fruit crops. - Tut, Gurkan (Cranfield University, 2019)
For sustainable agriculture, efficient usage of biocontrol agents (BCAs) is crucial. As BCAs are living organisms effective biocontrol ability is governed by complex ecological processes. Because of this, biocontrol of plant diseases can become constrained. Research on the ecology, mechanisms of action and population ecology in the phyllopshere environment is critical for modelling the efficacy of BCAs for control of foliar plant pathogens, especially Botrytis cinerea. The aim of the research was to obtain ecological knowledge on Bacillus subtilis QST 713 and Gliocladium catenulatum J1446, and if feasible use this ecological information to apply these two BCAs against B. cinerea. Thus the objective initially was to (i) develop a molecular based assay to quantify viable population changes of the two BCAs, and use this novel assay for investigating: (ii) the dose response relationship of B. cinerea to the bacterial and fungal BCA, (iii) impact of relative humidity (RH) and temperature used in UK agronomic production systems on BCA populations, (iv) produce a simple model to predict BCA fate, (v) identify the colonisation and dispersion kinetics of the two BCAs on expanding foliage, and finally from the collected ecological knowledge (vi) suggest optimisations strategies for the two BCAs. This study successfully developed a PMAxxᵀᴹ-qPCR method for quantifying the kinetics of viable population changes for both the BCAs. The dose response relationship of B. cinerea to the BCAs’ was deciphered and G. catenulatum median effective dose was 1 × 10⁸ spores/ml, while for B. subtilis this was 3 × 10⁸ CFUs/ml⁻¹ . However, this changed with temperature, formulation, and leaf tissue type. Both temperature and humidity impacted on viable population dynamics of the two BCAs, and showed that viable populations were sustained, increased or reduced depending on abiotic factors (temperature, R.H.), with efficacy best at conditions close to the BCAs optimum growth conditions. From the collected data, models were produced and tested for their ability to predict the fate of each BCA in commercial growing sites. The dispersion and colonisation kinetics of the two BCAs were analysed on growing lettuce and strawberry leaves. The two BCAs behaved in different ways, while their ability to disperse and colonise virgin leaf tissue was effective, the rate depended on the season (temperature and RH) and host. This study has developed significant new ecological knowledge on these two BCAs and their behaviour when applied to strawberry and lettuce leaf surfaces, and their establishment to control B. cinerea in these agronomic crop systems.
Keywords: Abiotic factors; Bacillus subtilis QST 713; biological control; Botrytis cinerea; climate; colonization; dew point; dispersion; dose of application; dose response models; dose; ecology; formulation; Gliocladium catenulatum J1446; grey mould disease; LD₅₀; lettuce; optimization; PMA; population density; population dynamics; predictive modelling; pre-harvest; preStop; qPCR; quantitative method; relative humidity; Sereande ASO; strawberry; temperature; viable cells; VPD